2013
DOI: 10.17221/7035-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Caudal approach and Mini TightRope system (mTR) application for the treatment of craniodorsal hip luxation in a cat: a case report

Abstract: The aim of this study was to evaluate the clinical and radiographic outcome of traumatic craniodorsal hip luxation in a cat, treated with the application of a Mini TightRope (mTR) implant. A caudal approach was carried out in order to expose the hip joint and the sciatic nerve preserving the muscle masses. Clinical follow-up and radiographic recheck were performed at 10 days, one, three, six and 12 months after surgery. Orthopaedic examination was normal 1 month after surgery while the revisit radiographs show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…Similarly, comparable rates of reluxation were encountered with both suture materials in our study. Overall, our results provide evidence that both UHMWPE and nylon are effective in the treatment of coxofemoral luxation in cats when using the HTS technique and corroborate findings of four previous reports 5,6,28,33 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, comparable rates of reluxation were encountered with both suture materials in our study. Overall, our results provide evidence that both UHMWPE and nylon are effective in the treatment of coxofemoral luxation in cats when using the HTS technique and corroborate findings of four previous reports 5,6,28,33 …”
Section: Discussionsupporting
confidence: 91%
“…Conversely, a moderate rate (24.4%) of postoperative complications was identified in our study; however, approximately half (11.1%) of these were minor and did not require intervention. No minor postoperative complications have been reported in previous studies in which HTS in cats is described 5,6,28,33 . The overall rate of postoperative complications in our study was similar 40 or lower 35 than that reported in dogs after HTS (26%–43%).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…7,8 Accordingly, numerous studies have described use of braided suture material systems for the treatment of coxofemoral luxation with success rates up to 94%. [9][10][11][12] In addition to using mechanically superior materials for toggle fixation of coxofemoral luxation, some surgeons have attempted to improve surgical technique. The currently recommended procedure involves drilling the femoral and acetabular bone tunnels separately.…”
Section: Introductionmentioning
confidence: 99%